How to Survive Mergers, Takovers and Other Corporate Disasters - Hirsh Paul (American : Addition Wesley Publishing Company, 1987)
Contents
Part 1: How wall street Helped kill Loyalty and commitment
Part 2: The new free agent manger
Keywords: Corporate Culture; United Stares